PENGETAHUAN DAN CARA MENGATASI MASALAH MESNTRUASI PADA SISWI SMAN 16 BEKASI - Nina Primasari; Juli Oktalia; Jujun Dwiastuti (IFI cabang Kota Bekasi, 2022)
Background : Menstruation is periodic and cyclical bleeding from the uterus accompanied by the release (desquamation) of the endometrium. Menstrual bleeding is the result of a complex interaction involving hormonal systems with body organs, namely the hypothalamus, pituitary, ovaries and uterus. Every woman has menstruation with a different cycle. The causes of irregular menstruation are from genetics and from an unfavorable lifestyle. Meanwhile, according to TCM, irregular menstruation is Yue Jing Bu Tiao. Although menstruation is a natural process, there are still many teenagers who consider menstruation to be sensitive and taboo to tell. Information about menstruation should be socialized as early as possible so that adolescents have good mental readiness in facing their periods and can carry out good self-care during menstruation. Objective : Increase knowledge and understanding of students of SMAN 16 Bekasi about Preparation, Management and How to Overcome Menstrual Problems. Method : The stages of implementation include preliminary survey, identification of facilities and infrastructure, implementation and evaluation. The activity will be held on Monday, October 17, 2022 offline using pocketbook media. Result : The activity was attended by 30 students from class X and class XI, lasting for 90 minutes. Activities include providing material on the concept of menstruation and how to overcome problems in menstruation. Participants were also given the opportunity to ask questions and answers. Conclusion : The activity went well and smoothly. It is hoped that young women can apply the knowledge received and can provide education also to their peers as a source of information about menstruation.